Activation of the Epithelial‐to‐Mesenchymal Transition Factor Snail Mediates Acetaldehyde‐Induced Intestinal Epithelial Barrier Disruption. (19th August 2013) - Elamin, Elhaseen; Masclee, Ad; Troost, Freddy; Dekker, Jan; Jonkers, Daisy
<x xml:space="preserve">Abstract</x> Background Acetaldehyde (AcH) is mutagenic and can reach high concentrations in colonic lumen after ethanol consumption and is associated with intestinal barrier dysfunction and an increased risk of progressive cancers, including colorectal carcinoma. Snail, the transcription factor of epithelial–mesenchymal transition, is known to down‐regulate expression of tight junction (TJ) and adherens junction (AJ) proteins, resulting in loss of epithelial integrity, cancer progression, and metastases. As AcH is mutagenic, the role of Snail in the AcH‐induced disruption of intestinal epithelial TJs deserves further investigation. Our aim was to investigate the role of oxidative stress and Snail activation in AcH‐induced barrier disruption in Caco‐2 monolayers. Methods The monolayers were exposed from the apical side to AcH ± L‐cysteine. Reactive oxygen species (ROS) generation and Snail activation were assessed by ELISA and immunofluorescence. Paracellular permeability, localization, and expression of ZO‐1, occludin, E‐cadherin, and β‐catenin were examined using transepithelial electrical resistance (TEER), fluorescein isothiocyanate–labeled dextran 4 kDa (FITC‐D4), immunofluorescence, and ELISA, respectively. Involvement of Snail was further addressed by inhibiting Snail using small interfering RNA (siRNA). Results Exposure to 25 μM AcH increased ROS generation and ROS‐dependently induced Snail phosphorylation. In addition, AcH increased paracellular permeability (decrease in TEER and increase in FITC‐D4 permeation) in association with redistribution and decrease of TJ and AJ protein levels, which could be attenuated by L‐cysteine. Knockdown of Snail by siRNA attenuated the AcH‐induced redistribution and decrease in the TJ and AJ proteins, in association with improvement of the barrier function. Conclusions Our data demonstrate that oxidative stress‐mediated Snail phosphorylation is likely a novel mechanism contributing to the deleterious effects of AcH on the TJ and AJ, and intestinal barrier function.